Obtaining a Fire-Resistant Coating Based on Acrylonitrile and Phosphoric Acid (Eurasian Journal of Physics,Chemistry and Mathematics, 2022)
Increasing the fire resistance of wooden structures is an important task that must be solved for their long and safe operation. When a wooden structure catches fire, it can collapse and burn completely in 20-30 minutes. Fire retardants allow you to slow down the burning process by 2-3 times and prevent serious consequences. During this time, necessary measures can be taken, people can be taken out, valuables can be saved.